2021
DOI: 10.1111/dme.14488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pregnancy outcomes in women with GCK‐MODY

Abstract: Aims To determine the fetal and maternal outcomes in pregnant women with Glucokinase‐Maturity onset diabetes of the young (GCK‐MODY). Methods We studied the obstetric and perinatal outcomes in 99 pregnancies of 34 women with GCK‐MODY. The mutation status of the offspring was known in 29 and presumed in 33. Clinical outcomes were determined and compared between affected (n = 39) and unaffected (n = 23) offspring. Results 59% of pregnancies were treated with diet alone and 41% received insulin. Birthweight, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…According to the Pedersen hypothesis (48), this suggested that accelerated fetal growth was induced by increased fetal insulin secretion by non-affected fetuses in response to maternal hyperglycemia, and that fetal growth was normal in affected fetuses since their insulin secretion was set at the same level as their mother's. Observational studies have consistently confirmed this report (41,42,(49)(50)(51)(52), and showed that the frequency of macrosomia (birthweight > 4000 g) and/or of LGA offspring were high (33-65%) in the first situation, as compared to the latter (4-13%, i.e. the expected rate of LGA in the general population) (Table 1).…”
Section: Unaffected Offspring Of Mothers With Gck-mody Are At High Risk Of Macrosomiasupporting
confidence: 66%
See 1 more Smart Citation
“…According to the Pedersen hypothesis (48), this suggested that accelerated fetal growth was induced by increased fetal insulin secretion by non-affected fetuses in response to maternal hyperglycemia, and that fetal growth was normal in affected fetuses since their insulin secretion was set at the same level as their mother's. Observational studies have consistently confirmed this report (41,42,(49)(50)(51)(52), and showed that the frequency of macrosomia (birthweight > 4000 g) and/or of LGA offspring were high (33-65%) in the first situation, as compared to the latter (4-13%, i.e. the expected rate of LGA in the general population) (Table 1).…”
Section: Unaffected Offspring Of Mothers With Gck-mody Are At High Risk Of Macrosomiasupporting
confidence: 66%
“…The Rate of Miscarriage Would Be Expected to Be Increased Given the Blood Glucose and HbA 1c Levels Observed in GCK-MODY Women It has been reported to be increased compared to that of the general population (33% of 56 pregnancies) in one study (40), but similar to the general population rate in a further study by the same group on a larger population (17% of 119 pregnancies) (41), and in an additional independent study (19% of 128 pregnancies) (42).…”
Section: Risks Associated With Pregnancy In Women With Gck-modymentioning
confidence: 74%
“…37 The birth weight for the infant in Case 2 was normal, despite her mother's history of diabetes diagnosed after screening in a previous pregnancy. Therefore, for a hyperglycemic infant of normal or low birth weight born to a mother with GDM, particularly where maternal hyperglycemia has failed to respond to insulin treatment in pregnancy 9,38 and persists postpartum, GCK-MODY is an important consideration. Neonatal hypoglycemia and macrosomia may be evident in the infant who has not inherited the same GCK mutation as their mother, 9 so a high birth weight and history of neonatal hypoglycemia in siblings may also provide a useful clue to the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…LGA-Rate (LGA: Large for Gestational Age) nicht reduzieren. Sie führte jedoch zu einer früheren Geburt und zu mehr neonatalen Hypoglykämien [12]. Ähnliches zeigte sich im US-amerikanischen MODY-Register [13].…”
Section: Diagnoseunclassified